(untitled) (Gumilyov Journal of Pedagogy, 2025)
Nowadays, internet users, especially students, frequently encounter threats such as phishing, identity theft, social engineering, malware, and cyberbullying. In this regard, it is crucial to investigate their cybersecurity awareness and identify effective teaching methods. This study employs the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, analyzing 20 scientific articles. All studies were sourced from the Scopus database, ensuring this review’s reliability and scientific validity. The results indicate varying levels of cybersecurity knowledge among students. The most commonly used methods to enhance students’ cybersecurity awareness include training sessions, game-based learning (gamification), interactive learning, surveys and tests, as well as monitoring and supervision. The study highlights the importance of integrating new approaches into the education system to foster a cybersecurity culture among students. Interactive teaching methods and practical lessons have proven to be particularly effective in improving students’ information security skills. This research contributes to the identification of effective strategies for enhancing students’ online security and serves as a foundation for improving cybersecurity education methodologies in the academic field.